BACTERIAL LYSATES FOR TOPICAL APPLICATION IN PREVENTION AND TREATMENT OF CHRONIC TONSILLITIS AMONG CHILDREN - T.I. Garashchenko; V.G. Volodarskaya ("Paediatrician" Publishers LLC, 2006)
The authors have carried on the research of the influence Imudon exerts (during topical application) on the run of chronic tonsillitis among 48 children aged between 5 and 10 years old, being dispensary registrants. The sublingual application of a medicine 6 pills daily within 20 days demonstrated the frequency reduction of chronic tonsillitis acerbations by 2.9 times, as well as the reduction of total need in systemic antibacterial treatment by 10 times. Apart from that, the frequency of S. pyogenes group a exposure reduced by 3 times. The researchers noticed the tendency to normalization of pharynx biocenosis. Thus, Imudon may be recommended for the daily courses of treatment to the people, suffering from chronic tonsillitis, palatine tonsil auxesis and recurrent tonsillo-pharyngites.Key words: chronic tonsillitis, children, prevention, bacterial lysates.